PENGARUH KEBIJAKAN DIVIDEN, KEBIJAKAN HUTANG, UKURAN PERUSAHAAN, DAN KEPUTUSAN INVESTASI TERHADAP NILAI PERUSAHAAN DI BEI PERIODE 2011-2015 - ASTIANAH (Jurnal Ilmu Manajemen (JIM), 2017)
The purpose of this research was to understand the influence of dividend policy, debt policy, firm size, and decision investment on company value. The object of this study were firm of consumer goods industry sector on BEI period 2011-2015. This research use kuantitative approach with secondary data. The population on this research consisted of 32 companies, the sample consisted of 9 companies that were taken using proposive sampling. The methods of data analysis in the research were multiple regression models. The result of this study indicated that, just a firm size variable have no significant relationship on firm value. While the threeth other variables such as dividend policy, debt policy, and investment decision variables which has a positive significant relationship on firm value. Keywords: dividend policy, debt policy, firm size, investment firm value